Inhibition of microRNA-214 ameliorates hepatic fibrosis and tumor incidence in platelet-derived growth factor C transgenic mice - Okada, Hikari (Cancer Sci, 2015)
Differentially regulated microRNA (miRNA) are associated with hepatic fibrosis; however, their potential usefulness for blocking hepatic fibrosis has not been exploited fully. We examined the expression of miRNA in the liver of a transgenic mouse model in which platelet-derived growth factor C (PDGF-C) is overexpressed (Pdgf-c Tg), resulting in hepatic fibrosis and steatosis and the eventual development of hepatocellular carcinoma (HCC). Robust induction of miR-214 correlated with fibrogenesis in the liver of Pdgf-c Tg mice, atherogenic high-fat diet-induced NASH mice, and patients with chronic hepatitis B or C. Pdgf-c Tg mice were injected with locked nucleic acid (LNA)-antimiR-214 via the tail vein using Invivofectamine 2.0 and the degree of hepatic fibrosis and tumor incidence were evaluated. Pdgf-c Tg mice treated with LNA-antimiR-214 showed a marked reduction in fibrosis and tumor incidence compared with saline or LNA-miR-control-injected control mice. In vitro, LNA-antimiR-214 significantly ameliorated TGF-β1-induced pro-fibrotic gene expression in Lx-2 cells. MiR-214 targets a negative regulator of EGFR signaling, Mig-6. Mimic-miR-214 decreased the expression of Mig-6 and increased the levels of EGF-mediated p-EGFR (Y1173 and Y845) and p-Met (Tyr1234/1235) in Huh-7 cells. Conversely, LNA-antimiR-214 repressed the expression of these genes. In conclusion, miR-214 appears to participate in the development of hepatic fibrosis by modulating the EGFR and TGF-β signaling pathways. LNA-antimiR-214 is a potential therapy for the prevention of hepatic fibrosis.